Coffee Shop Alternative Space for Expression Through Popular Culture Among Teenagers on the Outskirts of Cirebon - Devy Purwanti Darmawan; Faiz Yassar Hakim; Khaerudin Imawan (International Journal Labs, 2025)
Coffee Shops have evolved into social spaces that allow suburban teens to express themselves through popular culture. Coffee Shegia is a place that offers more than just drinks, but also a place for social interaction and cultural expression. Where suburban teenagers often face limited social space, the existence of a Coffee Shop provides a convenient alternative and supports their creativity. This study aims to analyze how Coffee Shegia functions as a social space that supports individual expression, social interaction, and engagement in popular cultural activities among adolescents. The space that must be mastered is; spatial space, spatial representation, and representation space. The research method used is a descriptive qualitative research method. The informants in this study were adolescents aged 17-30 years who had visited the Coffee Shop. Techniques used in data collection from primary and secondary sources through interviews and documentation. The results of the study show that Coffee Shegia is not only a place to enjoy coffee, but also a social space that allows teenagers to express themselves, create, and strengthen social relationships through various activities such as cake decoration, live music, and watching together. The design of the space that creates indoor and outdoor areas with supporting facilities such as Instagramable photo areas and billiards creates a friendly and comfortable togetherness, which supports positive interaction between individuals of different age groups. With a cozy atmosphere, Coffee Shegia not only increases social relationships, but can also form a deep social identity for its visitors.